Electronic Module With Project Based Learning (PjBL): Innovation Of Digital Learning Product On 4.0 Era - Titis Angga Rini; Putri Selfi Cholifah (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2020)
Digital teaching materials are one of the main needs in the field of education in this era 4.0. Digital teaching materials continue to be innovated in various forms such as e-modules in learning. Based on the needs, the purpose of this study was to develop e-modules collaborated with PjBL for the subject of basic learning skills. The results of the development of the collaboration between e-modules and PjBL received a good response from experts, educators, and students who were eligible as teaching materials. This development is one form of digital products that bridge current and future learning needs for students for training in using IT in the digital era in learning as prospective educators